Individualized tumor response testing profile has a prognostic value in childhood acute leukemias: multicenter non-interventional long-term follow-up study. Issue 6 (June 2013) - Piatkowska, Magdalena; Styczynski, Jan; Kolodziej, Beata; Kurylo-Rafinska, Beata; Kubicka, Malgorzata; Pogorzala, Monika; Czyzewski, Krzysztof; Debski, Robert; Matysiak, Michal; Malinowska, Iwona; Balwierz, Walentyna; Juraszewska, Edyta; et al.
Abstract: A total number of 817 children with acute lymphoblastic leukemia (ALL) and 181 with acute myeloblastic leukemia (AML) were assessed for individualized tumor response testing (ITRT) profile as a prognostic factor in long-term follow-up. For each patient, ITRT, initial response to therapy and long-term outcome were assessed. In initial ALL, an impact on long-term response was shown in ITRT for 13 drugs, while in initial AML only for cytarabine. For patients with ALL, a combined five-drug ITRT profile for prednisolone, l -asparaginase, vincristine, cytarabine and daunorubicin or doxorubicin had predictive value for probability of disease-free survival (pDFS) in univariate analysis, whereas in multivariate analysis, bone marrow response by day 33 was the only prognostic factor. For patients with AML, no factor had prognostic value for pDFS in univariate analysis, while ITRT to cytarabine almost reached significance. In conclusion, ITRT can possibly be regarded as a risk factor in childhood acute leukemias.